Catalytic intramolecular hydroamination of aminoallenes using titanium and tantalum complexes of sterically encumbered chiral sulfonamides. Issue 35 (27th August 2020) - Sha, Fanrui; Shimizu, Emily A.; Slocumb, Hannah S.; Towell, Sydney E.; Zhen, Yi; Porter, Hanna Z.; Takase, Michael K.; Johnson, Adam R.
Abstract : Titanium and tantalum catalysts supported by readily prepared chiral sulfonamide ligands catalyze hydroamination of aminoallenes that lack N -protecting groups. Abstract : Catalysis using earth abundant metals is an important goal due to the relative scarcity and expense of precious metal catalysts. It would be even more beneficial to use earth abundant catalysts for the synthesis of common pharmaceutical structural motifs such as pyrrolidine and pyridine. Thus, developing titanium catalysts for asymmetric ring closing hydroamination is a valuable goal. In this work, four sterically encumbered chiral sulfonamides derived from naturally occurring amino acids were prepared. These compounds undergo protonolysis reactions with Ti(NMe2 )4 or Ta(NMe2 )5 to give monomeric complexes as determined by both DOSY NMR and X-ray crystallography. The resulting complexes are active for the ring closing hydroamination hepta-4, 5-dienylamine to give a mixture of tetrahydropyridine and pyrrolidine products. However, the titanium complexes convert 6-methylhepta-4, 5-dienylamine exclusively to 2-(2-methylpropenyl)pyrrolidine in higher enantioselectivity than those previously reported, with enantiomeric excesses ranging from 18–24%. The corresponding tantalum complexes were more selective with enantiomeric excesses ranging from 33–39%.